The influence of the character peculiarities of the personality of the teacher on behavior in a conflict situation - A. S. Vasileva; A. S. Vokueva; A. A. Nikolaeva (Вестник университета, 2019)
In order to avoid confl in an educational organization, it is necessary to be able to identify correctly the personal characteristics of employees, to understand how different characterological features of the individual affect behavior, including in conflict situations and, taking into account the knowledge gained, to choose leadership styles, communication, to develop the foundations of corporate ethics. The concept of conflict, conflict situation, pre-conflict situation and accentuations of character has been considered in the article, the main functions and causes of the conflict have been revealed. The results of an empirical study of the teaching staff of an educational organization on the influence of the characterological features of the teacher’s personality on the strategy of behavior in a conflict situation have been adduced. The interrelation of character accentuations and choice of strategy of behavior in a conflict situation has been revealed.